Kallikrein-related peptidases (KLKs) and the hallmarks of cancer. (3rd July 2016) - Filippou, Panagiota S.; Karagiannis, George S.; Musrap, Natasha; Diamandis, Eleftherios P.
Abstract: The kallikrein-related peptidases (KLKs) represent the largest family of serine proteases within the human genome and are expressed in various tissues. Although they regulate several important physiological functions, KLKs have also been implicated in numerous pathophysiological processes, including cancer. Growing evidence describing the deregulation of KLK expression and secretion, as well as activation in various malignancies, has uncovered their potential as mediators of cancer progression, biomarkers of disease and as candidate therapeutic targets. The diversity of signalling pathways and proteolytic cascades involving KLKs and their downstream targets appears to affect cancer biology through multiple mechanisms, including those related to the hallmarks of cancer. The aim of this review is to provide an update on the importance of KLK-driven molecular pathways in relation to cancer cell traits associated with the hallmarks of cancer and to highlight their potential in personalized therapeutics.